2021
DOI: 10.4317/medoral.24132
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alternatives in the management of osteoradionecrosis of the jaws. Systematic review

Abstract: Background to systematically review the literature, comparing the healing of osteoradionecrosis (ORN) among the therapeutic alternatives: surgical, pharmacological and combined. Material and Methods The review was organized according to the PRISMA protocol with regards to the following PICO question: patients with ORN of the jaws (P=Patient); all interventions reported (I = intervention); between all therapies (C=Comparison); healing of lesions (O=outcome). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(60 citation statements)
references
References 7 publications
0
36
0
16
Order By: Relevance
“…Fixation plates and screws are removed if they appear to be a contributing factor. Studies have shown that early intervention with minor surgical procedures combined with pharmacological methods may improve the prognosis of ORN [ 51 ]. Surgical management is generally employed when conservative management is unsuccessful and there is progressive (Notani III) ORN resulting in pathological fractures and draining fistulae [ 52 ].…”
Section: Review Of the Conditionmentioning
confidence: 99%
“…Fixation plates and screws are removed if they appear to be a contributing factor. Studies have shown that early intervention with minor surgical procedures combined with pharmacological methods may improve the prognosis of ORN [ 51 ]. Surgical management is generally employed when conservative management is unsuccessful and there is progressive (Notani III) ORN resulting in pathological fractures and draining fistulae [ 52 ].…”
Section: Review Of the Conditionmentioning
confidence: 99%
“…Although conservative therapies can treat some early ORN, the cure rate is only 28.6%, combined surgery is required to obtain better effects, and the recurrence is possible [ 103 ]. Therefore, it is necessary to study a new treatment.…”
Section: Traditional Treatments Of Ornsmentioning
confidence: 99%
“…O uso dos fármacos, como a pentoxifilina-tocoferol (PENTO) ou associada ao clodronato (PENTOCLO), (Delanian et al, 2005) e a utilização de teriparatida (Cha et al, 2018) são formas de tratamento alternativo para a ORN, assim como os estudos realizados com fotobiomodulação antimicrobiana demonstraram potencializar, a fase de cicatrização dos tecidos acometidos por ORN (Camolesi et al, 2021).…”
Section: Fatores Predisponentes E Tratamentounclassified
“…Após a revisão dos títulos e resumos e eliminação das duplicatas, 189 estudos foram selecionados, dos quais 176 artigos foram excluídos após leitura do texto na íntegra (Figura 5.1). Finalmente, 13 artigos foram considerados para análise de qualidade metodológica (Fritz et al, 2010;Samman, 2011Samman, , 2012Bennett et al, 2016;Martos-Fernández et al, 2018;El-Rabbany et al, 2019;Kolokythas et al, 2019;Raggio;Winter, 2019;Abed et al, 2020;Beaumont et al, 2020;Lajolo et al, 2020;Zhang et al, 2020;Camolesi et al, 2021). O nível de concordância entre os examinadores na fase de inclusão e de elegibilidade foi de 0.9 e 0.9 (Kappa de Cohen), respectivamente.…”
Section: Elegibilidade Dos Estudosunclassified
See 1 more Smart Citation